2013
DOI: 10.1002/jmv.23865
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the IL28B Rs12979860 C/T polymorphism on the incidence and features of active cytomegalovirus infection in allogeneic stem cell transplant patients

Abstract: The current study was aimed at investigating whether the single nucleotide polymorphism (SNP) (rs12979860), upstream of the IL28B gene, had any effect on the incidence rate and the features of active CMV infection in the Allogeneic stem cell transplantation setting. This was a retrospective observational study including 151 patients undergoing T cell-replete Allo-SCT. Donor and recipient IL28 SNP genotype was determined by allele-specific real-time PCR. The incidence rate of active CMV infection was not signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 24 publications
3
46
0
Order By: Relevance
“…SNPs in these genes in donor and recipient have been associated with the occurrence of CMV reactivation, its duration, the peak levels of CMV DNAaemia and the development of CMV disease. [86][87][88][89] To date study findings have been inconsistent, limited by small numbers and mechanistic data is lacking. Larger confirmatory studies are required before recipient and donor SNPs can be to used for risk stratification or to guide therapeutic interventions.…”
Section: Factors Influencing CMV Immunity Post Transplantmentioning
confidence: 99%
“…SNPs in these genes in donor and recipient have been associated with the occurrence of CMV reactivation, its duration, the peak levels of CMV DNAaemia and the development of CMV disease. [86][87][88][89] To date study findings have been inconsistent, limited by small numbers and mechanistic data is lacking. Larger confirmatory studies are required before recipient and donor SNPs can be to used for risk stratification or to guide therapeutic interventions.…”
Section: Factors Influencing CMV Immunity Post Transplantmentioning
confidence: 99%
“…Allo-HSCT recipients that experienced acute GvHD and active CMV infection presented higher frequencies of the genotype T/T of the CD28 molecule. On the contrary, data from Bravo and collaborators seemed to point to a protective effect of the donor homozygous T allele of the IL-28B against CMV infection in allo-HSCT [100], which was supported by the study of Egli et al [101].…”
Section: Gene Polymorphismsmentioning
confidence: 55%
“…47 A study in CMV-seropositive kidney transplant patients 48 also found that the minor allele (T) at rs12979860 had a dominant beneficial effect against CMV replication. Although in another study in allogenic stem cell transplant recipients, 49 the minor allele T at rs12979860 protected recipients against CMV infection in a recessive model of inheritance. Two more studies have also reported on the association of IFNL SNPs with CMV.…”
Section: Cytomegalovirus Cytomegalovirus (Cmv) Is a Herpes Virus Thamentioning
confidence: 97%
“…Although two groups showed that their results fit best with a recessive model of inheritance of IFNL SNPs 50,51 in affecting CMV replication/retinitis wherein minor homozygosity was non-beneficial, the other three studies show an opposite trend where the minor allele had a beneficial effect against CMV replication in both patients and cell culture experiments, involving either dominant 47,48 or recessive models of inheritance. 49 In stark contrast, a dominant model of inheritance (of the non-beneficial IFNL SNP minor allele) has consistently given the best explanation on the observed phenotypes in association studies with both spontaneous clearance and IFN-based treatment response in chronic HCV infections. [11][12][13]15 This discrepancy within the CMV studies may be partly due to statistical fluctuations owing to low sample sizes, 47,50 and high heterogeneity among patient groups, end points and antiviral regimens that are followed in the different studies.…”
Section: Cytomegalovirus Cytomegalovirus (Cmv) Is a Herpes Virus Thamentioning
confidence: 99%